Industrialisation and Rural Livelihoods in China : Agricultural Processing in Sichuan. - Lingohr-Wolf, Susanne (Routledge contemporary China series., 2012)
Since the mid-1990s, "agricultural industrialisation" (AI) has been advocated in China to promote rural development by integrating agriculture with the post-harvest sectors such as agro-processing and marketing. Large-scale "Dragon head enterprises" (DHEs) and various forms of rural household associations (RAs) have been particularly promoted as AI organisational models. Drawing on the case study of the sweet potato sector in Sichuan Province, this book investigates their impact on rural livelihoods.